Endogean and cavernicolous Coleoptera of the Balkans. XXVIII. Synopsis of the subfamily Leptotyphlinae Fauvel, 1874 (Coleoptera, Staphylinidae) of the Balkan Peninsula, with the description of three new species from Serbia and Montenegro - Hlaváč, Peter; Janák, Jiří; Baňař, Petr (Zootaxa, 2025)
The actual knowledge on the staphylinid endogean subfamily Leptotyphlinae Fauvel, 1874 of the Balkan Peninsula is summarized. The subgenus Epirotyphlus Pace, 1995 is upgraded to the genus level resulting in two new combinations, Epirotyphlus leucadiensis (Pace, 1995) and E. zecevici (Pace, 1984). Three new species, Allotyphlus (Moreotyphlus) stolensis Hlaváč, Janák & Baňař, sp. nov., Epirotyphlus dusicae Hlaváč, Janák & Baňař, sp. nov. and Epirotyphlus janae Hlaváč, Janák & Baňař, sp. nov. are described. First record of Banatotyphlus siclus Struyve, 2022 for Serbia is given. The catalogue is provided for all Leptotyphlinae taxa of the Balkan Peninsula, which is to date represented by 4 tribes, 13 genera and 51 species. Keys are given for all tribes of the subfamily, to all genera of Metrotyphlini Coiffait, 1963 of the Palaearctic region and to all genera of Entomoculiini Coiffait, 1957, Leptotyphlini Fauvel, 1874 and Neotyphlini Coiffait, 1963 of the Balkan Peninsula. Maps of the distribution of Leptotyphlinae of the Balkan Peninsula are also presented.